Does easy start-up formation hamper incumbents' R&D investment? A theoretical and empirical analysis - Luca Colombo; Herbert Dawid; Mariacristina Piva; Marco Vivarelli (Institute for the Study of Labor (IZA), 2013)
This paper investigates, both theoretically and empirically, the implications that complementary assets needed for the formation of start-ups - proxied by the ease of access to financial resources - have on the innovative efforts of incumbent firms. In particular, we develop a theoretical model, highlighting a strategic incentive effect by which the innovative efforts of incumbent firms are decreasing in the availability of the complementary assets needed for the creation of a start- up. The empirical relevance of this effect is investigated by using firm level data drawn from the third Italian Community Innovation Survey covering the period 1998-2000. The results of our empirical analysis support our theory-based insights.
Keywords: O31; L26; 330; R&D; innovation; start-up; complementary assets